ANALISIS PENERAPAN SISTEM ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI PADA USAHA KECIL MENENGAH (UKM) (STUDI KASUS PADA UD. TAHU SUTRA) (Fakultas Ekonomi Universitas Gresik, 2017)
Small and Medium Enterprises (SMEs) are an important part of an economy. Competition in the global world today requires SMEs to improve the efficiency and effectiveness of their production processes in order to improve competitiveness. Cost of production has a very important role in determining the selling price of the product, the proper costing will result in more cost of production more accurate. This study aims to determine the cost of production of white tofu, fried tofu and tempe based on Activity Based Costing system at UD. TAHU SUTRA which still use conventional system. This research uses descriptive qualitative method. The result of research is the determination of cost of production based on Activity Based Costing system on white tofu Rp. 149.314.294 whereas when using a conventional system of Rp. 174.228.374, with the difference of Rp. 24.914.080 or 14% (overvalue). Meanwhile, to know the fried calculation of the cost of production based on Activity Based Costing system of Rp. 89.486.009,3, while when using a conventional system of Rp. 102,811,397 with difference of Rp. 13.325.387,7 or 13% (overvalue). And for the cost of production of tempe by using Activity Based Costing system of Rp. 57.013.298,5 whereas when using conventional system harag principal production of Rp. 79.416.150 with the difference of Rp. 22.402.851.5 or 28% (overvalue).ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477673